Implementasi Kurikulum Merdeka Belajar di Daerah Kepulauan: Studi Kasus di SMA Negeri 1 Kepulauan Sula - Bakri Titdoy; Decky W. Kamagi; Jantje Ngangi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to evaluate the implementation of the Independent Learning Curriculum at SMA Negeri 1 Sula Islands, an educational institution located in the archipelago with its own geographical characteristics and challenges. The focus of this study is to assess the effectiveness of curriculum implementation in shaping a flexible, participatory, and contextual learning experience. Using a descriptive quantitative approach, data was collected through questionnaires of school principals, vice principals for curriculum and student affairs, and grade XI science and social studies students. The results of the study showed that all respondents from school management gave an assessment of the "Very Good" category to the implementation of the Independent Curriculum. Meanwhile, students in grade XI Science gave 92% of responses in the "Very Good" category, and students in grade XI Social Studies recorded 74% in the same category, with a small percentage being in the "Poor" category. These findings indicate that the Independent Curriculum approach that emphasizes project-based learning, learning differentiation, and formative assessment has been successfully adapted effectively by teachers and students. Teacher training support, availability of facilities, and adaptation to the local context have all contributed to this success. The implications of this study show that the Independent Curriculum can be effectively implemented in the archipelago if supported by visionary school leadership and continuous training. This study makes an empirical contribution to the national education reform literature and opens further research opportunities on curriculum adaptation in the 3T region.